COVID-19 vaccine effectiveness among healthcare workers in Albania (COVE-AL): protocol for a prospective cohort study and cohort baseline data. Issue 3 (23rd March 2022) - Sridhar, Shela; Fico, Albana; Preza, Iria; Hatibi, Iris; Sulo, Jonilda; Kissling, Esther; Daja, Rovena; Ibrahim, Rawi; Lemos, Diogo; Rubin-Smith, Julia; Schmid, Alexis; Vasili, Adela; et al.
Abstract : Introduction: Critical questions remain about COVID-19 vaccine effectiveness (VE) in real-world settings, particularly in middle-income countries. We describe a study protocol to evaluate COVID-19 VE in preventing laboratory-confirmed SARS-CoV-2 infection in health workers (HWs) in Albania, an upper-middle-income country. Methods and analysis: In this 12-month prospective cohort study, we enrolled HWs at three hospitals in Albania. HWs are vaccinated through the routine COVID-19 vaccine campaign. Participants completed a baseline survey about demographics, clinical comorbidities, and infection risk behaviours. Baseline serology samples were also collected and tested against the SARS-CoV-2 spike protein, and respiratory swabs were collected and tested for SARS-CoV-2 by RT-PCR. Participants complete weekly symptom questionnaires and symptomatic participants have a respiratory swab collected, which is tested for SARS-CoV-2. At 3, 6, 9 months and 12 months of the study, serology will be collected and tested for antibodies against the SARS-CoV-2 nucleocapsid protein and spike protein. VE will be estimated using a piecewise proportional hazards model (VE=1−HR). Baseline data: From February to May 2021, 1504 HWs were enrolled. The median age was 44 (range: 22–71) and 78% were female. At enrolment, 72% of participants were seropositive for SARS-CoV-2. 56% of participants were vaccinated with one dose, of whom 98% received their first shot within 4 days of enrolment. All HWs received the Pfizer BNT162b2 mRNA COVID-19 vaccine. Ethics and dissemination: The study protocol and procedures were reviewed and approved by the WHO Ethical Review Board, reference number CERC.0097A, and the Albanian Institute of Public Health Ethical Review Board, reference number 156. All participants have provided written informed consent to participate in this study. The primary results of this study will be published in a peer-reviewed journal at the time of completion. Trial registration number: NCT04811391 .